Author Guidelines - Yunisrina Qismullah Yusuf (Universitas Syiah Kuala, 2014)
Guidelines for Article Submission   SiELE journal accepts articles on research and development in the field of teaching and learning of English, linguistics, educational development, policy and cultural studies in education. To be considered for publication, the article should be presented in the following system: First page: include a title page with the full title of the paper (must not exceed 16 words), the author(s') name(s), affiliation(s), phone number(s) and e-mail address of the corresponding author. A brief bio-data of the author(s) (maximum of 100 words) is provided in this page. Second page and subsequent page: Submissions should be between 4000-6000 (including abstract, table(s), figure(s) and references) in A4 size paper with margins as the following: top 3 cm, bottom 3 cm, right 2.5 cm and left 4 cm. The font is Times New Roman, size 12 and single spaced. The article should generally consist of the following sections: introduction, review of literature, method, findings, discussion and conclusion. Headings and subheadings should be presented as follows (provide a space between the headings and sub-headings). 1         INTRODUCTION 1.1      Subheading of the content  1.1.1   Subheading of the content  For Tables, the title size is 12 and the content size is 10. Please number the tables subsequently throughout your article and the title is written above the table. For Figures, the title size is 12 and the content size (if any) is 10. Please number the figures subsequently throughout your article and the title is written below the figure. The reference list should be arranged alphabetically following the guidelines of the Publication Manual of the American Psychological Association (5th ed.). See the following examples:   Book: Ellis, R. (2003). Task-based language learning and teaching. Oxford: Oxford University Press. Internet source: Andrewes, S. (2003). Group work v. whole-class activities. Retrieved October 1, 2012 from http://www.teachingenglish.org.uk/think/articles/group-work-v-whole-class-activities Journal: Yusuf, Y. Q., Pillai, S., & Mohd. Ali, N.T.A. (2013). Speaking Acehnese in Malaysia. Language and Communication, 33(1): 50-60. Chapter in an edited volume: Lee, E. M., & Lim, L. (2000). Diphthongs in Singaporean English: Their realizations across different formality levels, and some attitudes of listeners towards them. In A. Brown, D. Deterding & E. L. Low (Eds). The English language in Singapore: Research on pronunciation (pp. 101-111). Singapore: Singapore Association for Applied Linguistics. Conference proceedings publications: Al-Tamimi, J., & Ferragne, E. (2005). Does vowel space size depend on language vowel inventories? Evidence from two Arabic dialects and French. Proceedings of Interspeech (pp. 2465-2468). Lisbon, Portugal. Published dissertation: Asyik. A. G. (1987). A contextual grammar of Acehnese sentences. (Doctoral dissertation). University of Michigan, Ann Arbor. Retrieved February 4, 2014 from http://www.acehbooks.org/pdf/00402.pdf. (Order number: 8720237) Unpublished thesis/dissertation: Yasin, B. (2004). Sistem informasi manajemen pendidikan: Studi pengembangan model sistem informasi manajemen bidang adminsitrasi akademik dan kemahasiswaan pada FKIP Unsyiah. (Unpublished doctoral dissertation). Universitas Negeri Malang Malang.   Unpublished paper presented at a conference: Yasin, B. (2007, December). Membangun masa depan pendidikan Aceh Barat: Strategi dan kebijakan. Paper presented at the Seminar Pembangunan Pendidikan Kabupaten Aceh Barat, Universitas Syiah Kuala, Banda Aceh, Indonesia. Mass media/newspaper: Akmal, S. (2011, March 13). Nasib Bahsa Aceh di tengah euforia nasionalisme Keacehan. Serambi Indonesia, p. Opini column.   For in-text citations, use the name of the author(s) followed by the year of publication.  Submit the article to sielejournal@gmail.com, with the subject: SUBMISSION TO SiELE. For further information on the submission guideline, please visit our page at http://www.jurnal.unsyiah.ac.id/SiELE. Once your article is accepted, the publication fee is Rp. 250.000,-.